2019
DOI: 10.3727/108354219x15525055915518
|View full text |Cite
|
Sign up to set email alerts
|

Online Reputation and Destination Competitiveness: The Case of Spain

Abstract: a conceptual model in which promotion (including reputation), branding, and pricing constitute drivers of destination competitiveness. A positive reputation enhances the competitiveness of a destination, favoring its attractiveness and therefore the potential demand to visit it (Komsic & Dorcic, 2016). Consequently, tourist destinations dedicate a considerable amount of resources to improve their image (Hong, 2009) and, in this context, many destination management organizations (DMOs) are making a considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Foroudi, Cuomo, Foroudi, et al (2019) found that the reputation and the image of heritage characteristics in tourism destination could improve the attraction to tourists and intensify their tourism intention of tourists. Perles-Ribes et al (2019) analyzed the relationship between online reputation and tourism competitiveness of Spanish coastal tourism destinations based on tourists' comments on social media and found that good online reputation of tourism destinations had a positive effect on tourists' tourism tendency and helped to improve the competitiveness of tourism destinations. These studies mainly focus on the analysis of the impact of the reputation of the tourism destination on the posttourism but do not analyze the impact on the decision-making of tourists in the tourism.…”
Section: Introductionmentioning
confidence: 99%
“…Foroudi, Cuomo, Foroudi, et al (2019) found that the reputation and the image of heritage characteristics in tourism destination could improve the attraction to tourists and intensify their tourism intention of tourists. Perles-Ribes et al (2019) analyzed the relationship between online reputation and tourism competitiveness of Spanish coastal tourism destinations based on tourists' comments on social media and found that good online reputation of tourism destinations had a positive effect on tourists' tourism tendency and helped to improve the competitiveness of tourism destinations. These studies mainly focus on the analysis of the impact of the reputation of the tourism destination on the posttourism but do not analyze the impact on the decision-making of tourists in the tourism.…”
Section: Introductionmentioning
confidence: 99%
“…The online reputation of destinations and of all their elements has a considerable effect on their competitiveness [62,63] as is mentioned in numerous studies. It has become a tool for creating an image of any destination, especially at a time such as the present when smart destinations prevail [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Tourists' purchasing behavior of online tourism products is not only affected by the tangible characteristics of tourism products. Impalpable product features [79] such as the guarantee of products and promotion methods [60], as well as channel-related factors like online reviews [61,62] and the credit rating of merchants [77] also count. These indicators are controlled in this paper.…”
Section: Research Methods and Data Descriptionmentioning
confidence: 99%
“…Second, as for the effects of reputation on sales, reputation significantly affects the consumer's perception of trust [75] and thereby enhances a firm's performance [76]. Francisco et al (2019) suggest that a destination's online reputation plays a key role in promoting its competitiveness [77]. In this study, we use the credit rating of merchants as a proxy for a merchant's reputation.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%